TasiRNA-ARF Pathway Moderates Floral Architecture in Arabidopsis Plants Subjected to Drought Stress. (26th August 2014) - Matsui, Akihiro; Mizunashi, Kayoko; Tanaka, Maho; Kaminuma, Eli; Nguyen, Anh Hai; Nakajima, Maiko; Kim, Jong-Myong; Nguyen, Dong Van; Toyoda, Tetsuro; Seki, Motoaki
Abstract : In plants, miRNAs and siRNAs, such as transacting siRNAs (ta-siRNAs), affect their targets through distinct regulatory mechanisms. In this study, the expression profiles of small RNAs (smRNAs) in Arabidopsis plants subjected to drought, cold, and high-salinity stress were analyzed using 454 DNA sequencing technology. Expression of three groups of ta-siRNAs (TAS1, TAS2, and TAS3) and their precursors was downregulated in Arabidopsis plants subjected to drought and high-salinity stress. Analysis of ta-siRNA synthesis mutants and mutated ARF3 -overexpressing plants that escape the tasiRNA-ARF target indicated that self-pollination was hampered by short stamens in plants under drought and high-salinity stress. Microarray analysis of flower buds of rdr6 and wild-type plants under drought stress and nonstressed conditions revealed that expression of floral development- and auxin response-related genes was affected by drought stress and by the RDR6 mutation. The overall results of the present study indicated that tasiRNA-ARF is involved in maintaining the normal morphogenesis of flowers in plants under stress conditions through fine-tuning expression changes of floral development-related and auxin response-related genes.